العلاقة بين التمكين الاقتصادي للمرأة والنمو الاقتصادي في مصر: The Relationship Between Economic Empowerment of Women and Economic Growth in Egypt - محمد عبد العظيم أحمد محمد (Journal of North African Economies, 2025)
The study aims to test the causal relationship between women’s economic empowerment and economic growth in Egypt during the period (1990-2020 ), The study is based on the hypothesis,that there is a causal two-way relationship between economic empowerment and real GDP, The validity of the hypothesis was tested by relying on the inductive method in collecting study data,and the validity of the study hypothesis was tested using the VECM error correction model, The results of the study found that the direction of the sui generis relationship in the long and short term is one-way from women's economic empowerment to real GDP, meaning that women's economic empowerment causes real GDP in the short and long terms._